International mass gatherings and travel-associated illness: A GeoSentinel cross-sectional, observational study. Issue 32 (November 2019) - ,; Gautret, Philippe; Angelo, Kristina M.; Asgeirsson, Hilmir; Duvignaud, Alexandre; van Genderen, Perry J.J.; Bottieau, Emmanuel; Chen, Lin H.; Parker, Salim; Connor, Bradley A.; Barnett, Elizabeth D.; Libman, Michael; et al.
Abstract: Background: Travelers to international mass gatherings may be exposed to conditions which increase their risk of acquiring infectious diseases. Most existing data come from single clinical sites seeing returning travelers, or relate to single events. Methods: Investigators evaluated ill travelers returning from a mass gathering, and presenting to a GeoSentinel site between August 2015 and April 2019, and collected data on the nature of the event and the relation between final diagnoses and the mass gathering. Results: Of 296 ill travelers, 51% were female and the median age was 54 years (range: 1–88). Over 82% returned from a religious mass gathering, most frequently Umrah or Hajj. Only 3% returned from the Olympics in Brazil or South Korea. Other mass gatherings included other sporting events, cultural or entertainment events, and conferences. Respiratory diseases accounted for almost 80% of all diagnoses, with vaccine preventable illnesses such as influenza and pneumonia accounting for 26% and 20% of all diagnoses respectively. This was followed by gastrointestinal illnesses, accounting for 4.5%. Sixty-three percent of travelers reported having a pre-travel encounter with a healthcare provider. Conclusions: Despite this surveillance being limited to patients presenting to GeoSentinel sites, our findings highlight the importance of respiratory diseases at mass gatherings, the need for pre-travel consultations before mass gatherings, and consideration of vaccination against influenza and pneumococcal disease.